Growing Burden of Stroke, Recent Advancements in Management and Global Commitments: The Way Forward - Nambiar, Vivek; Sudevan, Remya; Ajai, Amrutha; Chattu, Vijay Kumar (Journal of Pharmacy Practice and Community Medicine)
Worldwide, cerebrovascular accidents (stroke) are the second leading cause of death and the third leading cause of disability. Strokes mainly affect individuals at the peak of their productive life. Despite its enormous impact on countries’ socio-economic development, this growing crisis has received very little attention to date.[1] In order to achieve the UN Sustainable Development Goal 3 which aims for a 30% reduction in non-communicable diseases by 2030, it requires a substantial reduction in cardiovascular diseases. Especially the secondary prevention of recurrent myocardial infarction and stroke among those with known cardiovascular disease can reduce cardiovascular mortality and morbidity. The cost-effectiveness of secondary prevention of cardiovascular disease,[2] coupled with lifestyle changes, has long been established and it is the need of the hour to apply the recent advancements in emergency management of stroke to decrease mortality, morbidity and improve the quality of life.